Enhancement of thermoelectric properties by lattice softening and energy band gap control in Te-deficient InTe1−δ - Song Yi Back; Hyunyong Cho; Young-Kwang Kim; Seokyeong Byeon; Hyungyu Jin; Kunihito Koumoto; Jong-Soo Rhyee (AIP Advances, 2018)
The InTe has intrinsically low lattice thermal conductivity κL originating from the anharmonic bonding of In1+ ion in the lattice, which scatters the phonons. Here we report the enhancement of thermoelectric properties in Te-deficient InTe1−δ (δ = 0, 0.01, 0.1, and 0.2) polycrystalline compounds by lattice softening and energy band gap opening. Te-deficiency gives rise to more weak chemical bonding between In1+ atoms and In3+Te2− clusters than those of pristine InTe, resulting in the reduction of κL near the room temperature. The weak ionic bonding is confirmed by the increase of lattice volume from the X-ray diffraction and lattice softening by the decrease of Debye temperature with increasing Te-deficiency. We observed the low lattice thermal conductivity κL of 0.53 W m−1 K−1 at 300 K for InTe0.99, which is about 25 % decreased value than those of InTe. The Te-deficiency also induces energy band gap so that the electrical resistivity and Seebeck coefficient are increased due to the decrease of carrier concentration. Temperature-dependent thermoelectric properties shows the high Seebeck coefficient at high temperature and high electrical conductivity near room temperature, resulting in the temperature-insensitive high power factor S2σ over a wide temperature range. Owing to the temperature-insensitive high power factor and intrinsic low lattice thermal conductivity by Te-deficiency, the thermoelectric performances of figure-of-merit ZT and engineering ZTeng are enhanced at mild temperature range (≤550 K).